Renal Leiomyoma: Ultrasonography and Computed Tomography Features with Histopathologic Correlation - Onur, Mehmet Ruhi; Akin, Mehmet Mustafa; Onur, Ahmet Rahmi (Aves, 2013)
Renal leiomyomas are not uncommon mesenchymal neoplasms of the kidney, found in 5% of autopsy specimens and comprising 0.3% of all treated tumors. These tumors arise from the smooth muscle cells of the kidney and are mostly located in the renal capsule. Typical imaging features of renal leiomyomas include a peripheral location, welldefined margins, and hyperattenuation on nonenhanced computed tomography (CT) images. The differential diagnosis of renal leiomyomas includes benign and malignant solid neoplasms of the kidney. Familiarity with typical renal leiomyoma imaging findings may help in the management of these patients and prevent unnecessary surgery.
Renal leomyom: Ultrasonografi ve bilgisayarli{dotless} tomografi bulgulari{dotless} i?le histopatolojik korelasyon
Keywords: Leiomyoma; kidney; ultrasonography; computed tomography